Coldplay Concert Rejection in Indonesia An Analysis of Islamic Identity Mobilization - Ibrahim, Muhammad Faris (LP2M IAIN kUDUS, 2024)
Islam is not only a religion but also an identity for its believers. The fact that Islam is an identity made it subject to ongoing reinterpretation and reconstruction based on the context by certain actors. Therefore, through this article, the author aims to examine the mobilization of Islamic identity within the context of the Coldplay concert rejection by The 212 Alumni Brotherhood (PA) and other Islamist groups with aligned ideologies. This qualitative study, based on library research from journals, books, and media reports, applies historical and political approaches to analyze Islamic identity mobilization in Indonesia, focusing on data surrounding the Coldplay concert rejection within recent political contexts. The author finds that the rejection phenomenon is the result of the contestation of Islamic identity that has been contested in Indonesia and the strengthening of political Islam identity. Indications of strengthening this identity can be seen from the rise of identity politics in the general elections in recent years. And finally, the author concludes that the rejection of the Coldplay concert is an effort to mobilize Islamic identity as the majority in Indonesia, which in turn has contributed to causing discriminatory actions against minority communities.AbstrakIslam bukan hanya agama, tetapi juga identitas bagi para pemeluknya. Fakta bahwa Islam adalah identitas menjadikannya terus mengalami reinterpretasi dan rekonstruksi berdasarkan konteks tertentu oleh para aktor tertentu. Oleh karena itu, melalui artikel ini, penulis bertujuan untuk mengkaji mobilisasi identitas Islam dalam konteks penolakan konser Coldplay oleh Persaudaraan Alumni 212 (PA) dan kelompok Islamis lain yang memiliki ideologi sejalan. Penelitian kualitatif ini, berdasarkan studi pustaka dari jurnal, buku, dan laporan media, menerapkan pendekatan historis dan politis untuk menganalisis mobilisasi identitas Islam di Indonesia, dengan fokus pada data terkait penolakan konser Coldplay dalam konteks politik terkini. Penulis menemukan bahwa fenomena penolakan ini merupakan hasil kontestasi identitas Islam yang terus diperebutkan di Indonesia serta penguatan identitas politik Islam. Indikasi penguatan identitas ini terlihat dari meningkatnya politik identitas dalam pemilu beberapa tahun terakhir. Akhirnya, penulis menyimpulkan bahwa penolakan konser Coldplay adalah upaya mobilisasi identitas Islam sebagai mayoritas di Indonesia, yang pada gilirannya turut berkontribusi terhadap tindakan diskriminatif terhadap kelompok minoritas.